Fault Slip and Exhumation History of the Willard Thrust Sheet, Sevier Fold‐Thrust Belt, Utah: Relations to Wedge Propagation, Hinterland Uplift, and Foreland Basin Sedimentation. Issue 8 (13th August 2019) - Yonkee, W. A.; Eleogram, B.; Wells, M. L.; Stockli, D. F.; Kelley, S.; Barber, D. E.
Abstract: Zircon (U‐Th)/He (ZHe) and zircon fission track thermochronometric data for 47 samples spanning the areally extensive Willard thrust sheet within the western part of the Sevier fold‐thrust belt record enhanced cooling and exhumation during major thrust slip spanning approximately 125–90 Ma. ZHe and zircon fission track age‐paleodepth patterns along structural transects and age‐distance relations along stratigraphic‐parallel traverses, combined with thermo‐kinematic modeling, constrain the fault slip history, with estimated slip rates of ~1 km/Myr from 125 to 105 Ma, increasing to ~3 km/Myr from 105 to 92 Ma, and then decreasing as major slip was transferred onto eastern thrusts. Exhumation was concentrated during motion up thrust ramps with estimated erosion rates of ~0.1 to 0.3 km/Myr. Local cooling ages of approximately 160–150 Ma may record a period of regional erosion, or alternatively an early phase of limited (<10 km) thrust slip. Propagation of the Sevier wedge front and major thrust slip during the late Early to mid‐Cretaceous were synchronous with increasing subsidence and deposition of thick synorogenic strata in the foreland, crustal thickening in the hinterland, growing igneous activity in the Sierran magmatic arc, and increasing plate convergence rates. Along‐strike, other parts of the Cordilleran retroarc fold‐thrust belt also experienced major shortening during the late Early to mid‐Cretaceous, following a period of earlier Cretaceous quiescence. Late Jurassic shortening was concentrated nearer the arc, and thus mostly in the hinterland at the latitude of northern Utah, related to width and location of the passive‐margin sedimentary wedge relative to the plate margin. Key Points: New thermochronometric data constrain the fault slip and exhumation history of the Willard thrust sheet, western Sevier belt Major slip on the Willard thrust from 125 to 90 Ma was synchronous with increased foreland sedimentation and hinterland crustal thickening Fault‐slip histories of dominant thrust sheets in the Sevier belt reflect evolving plate margin dynamics and primary crustal architecture